Schools and Universities in Audiovisual Media: Experts’ Opinions - Fedorov, Alexander (Communication Today, 2025)
The objects of the research (as part of the project School and University in the Mirror of Soviet, Russian and Western Audiovisual Media Texts), are the opinions of international experts (media educators, researchers, media critics, media culture public figures) about the development of the school and university topic in the mirror of audiovisual media texts, about the transformation of basic concepts and stereotypical models of the school and university theme into media. The main hypothesis of the research is that the opinions of international experts will be based on the classification and comparative analysis of content models, genre modifications, stereotypes of media texts (feature films, documentaries, TV programmes, websites, etc.), related to the interpretation of the topic of school and university, and helped to confirm and refine the earlier theoretical model of audiovisual media texts on the subject of school and university. This model includes such structural components as the historical period of events in the media text; the environment; household items; methods of depicting reality; the traits of the main characters – teachers and students (their values, ideas, clothing, vocabulary, facial expressions, gestures, etc.); significant changes in the lives of characters; problems encountered and options on solving these problems.